Retrospective PCR-based species identification of Leishmania in two patients with visceral leishmaniasis in Serbia - Dakić, Zorica; Nielsen, Henrik Vedel; Pavlović, Milorad; Poluga, Jasmina; Stevanović, Goran; Lavadinović, Lidija; Milošević, Branko; Pelemiš, Mijomir; Urošević, Aleksandar; Jovanović, Snežana; Stensvold, Christen Rune (JMM Case Reports, 2016)
Introduction: Retrospective molecular identification of Leishmania parasites in two patients with visceral leishmaniasis (VL) previously treated in Serbia was carried out. DNA was isolated from unstained bone marrow smears (BMSs) kept for 11 and 8 years. Genus-specific real-time PCR was combined with conventional PCR and sequencing for detection and species identification. Case presentation: In 2003, a 40-year-old Serbian male was admitted to the Clinical Centre of Serbia (CCS) with fever, sweating, fatigue and splenomegaly, which developed over a period of 7 weeks. He had frequently travelled around Europe. VL was confirmed by microscopy of Giemsa-stained BMS. Treatment by pentavalent antimonials was successfully completed. Two years later, the patient developed post-kala-azar dermal leishmaniasis. Treatment resulted in symptom resolution. Later on, Leishmania infantum was identified as the causative agent of the VL by sequencing of the ITS (internal transcribed spacer) region; mixed Leishmania spp. infection could not be excluded. In 2006, a 33-year-old female from Vojvodina, Serbia, with pre-existing diabetes mellitus and chronic meningoencephalitis and a history of frequent visits to the Montenegrin seacoast, was admitted to the CCS with fever, pancytopenia and moderate hepatosplenomegaly. A stained BMS revealed abundant Leishmania amastigotes. Indirect haemagglutination analysis was positive with a titre of 1 : 2048, and a rapid dipstick rK39 test was also positive. Treatment by liposomal amphotericin B was successful; however, shortly after, the patient developed neural infection and pneumonia and died. The causative agent was identified as L. infantum. Conclusion: Molecular diagnosis of VL and species delineation using DNA from unstained BMSs stored for several years is possible.
Keywords: Leishmania infantum